Big data: techniques and technologies in Geoscience - Chapman, Nicolas (New York Larsen & Keller, 2023)
Big data refers to a collection of data that is enormous in volume and is expanding at exponential rates with the passage of time. It is a dataset that is too large and complex for traditional data management tools to process or store it effectively. There are various types of big data including semi-structured, structured and unstructured. Big data technologies are used in a number of industries and fields including banking, communication, healthcare, geosciences, astrophysics, and trade. The geographic information systems (GISs) are an important application of big data in geosciences, which aid in creating, managing, analyzing and mapping all types of geospatial data. GISs generate huge amounts of data, which are analyzed using big data technologies. Big data computing for GIS data enables analysis and decision making from massive datasets by using spatiotemporal data mining, algorithms and query processing. This book elucidates the concepts and innovative models around prospective developments with respect to big data techniques and technologies used in geoscience. It will serve as a reference to a broad spectrum of readers.
Keywords: Geology--Data processing; Big data; Geology--technological innovations